The Calling of Paradise On Earth: Marketing Mix Factors Analysis for Foreign Tourists in Bali - I Dewa Made Agung Kertha Nugraha; P. Paulina (Jurnal Ilmu Manajemen & Ekonomika, 2014)
Purpose – For the past decade, cultural resources and tourism have become inextricably linked throughout the world especially in developing countries. This study aims at determining the factors of Bali tourism marketing mix priority for foreign tourist. Design/methodology/approach – The research applied a quantitative method and employed an Analytical Hierarchy Process (AHP) for examining the dominant factors based on data collected from97 foreign tourists who fulfilled the questionnaires.Findings – The findings of the study reveal that marketing mix factors that has the highest value from foreign tourist about Bali tourism is the price factor with a weight of 0.200 followed by product factor (0,160), promotion factor (0,159), people (0,134), physical evidence (0,123), process (0,166), and the last position is placed factor which has a weight of (0,107).